Epidemiology and Associated Risk Factors for Brucellosis in Small Ruminants Kept at Institutional Livestock Farms in Punjab, Pakistan - Ullah, Qudrat; Jamil, Tariq; Melzer, Falk; Saqib, Muhammad; Hussain, Muhammad Hammad; Aslam, Muhammad Aamir; Jamil, Huma; Iqbal, Muhammad Amjad; Tahir, Usman; Ullah, Shakeeb; Qureshi, Zafar Iqbal; Schwarz, Stefan; et al. (Frontiers in Veterinary Science, 2020)
Brucellosis is considered as an endemic infection in ruminants in Pakistan. Both Brucella abortus and B. melitensis infections have been reported in domestic animals and humans in the country. This study aimed to identify the burden of anti-Brucella antibodies in small ruminants as well as potential risk factors associated with its occurrence at nine institutional livestock farms. A total of 1000 sera (500 sheep and 500 goats) were collected. Samples were screened by indirect-ELISA for anti-smooth-Brucella antibodies followed by serial detection by real-time PCR. Overall, 5.1% (51/1000) of the sera were found seropositive for the antibodies with 5% (25/500) prevalence in goats and 5.2% (26/500) in sheep. Brucella-DNA was not detected by real-time PCR in any of the tested sera. No significant association was observed between seropositivity and sex or species of the animals. Multiple logistic regression model indicated that small ruminats; kept at farm 2 (OR 34.05), > 4 years of age (OR 2.88), with history of reproductive disorders (OR 2.69), and with BCS of less than or equal to 3 (OR 12.37) were more likely to test positive for the brucellosis at these farms. We suggest that farm biosecurity and brucellosis-screening programs should be improved at these farms.